Corporate identity management in Malaysian higher education sector: developing a conceptual model - Mohamad, Bahtiar; Abu Bakar, Hassan; Ismail, Ahmed Rageh; Halim, Haslina; Bidin, Rosmiza (2016)
Corporate identity management (CIM) in universities has been acknowledged in marketing literature as an important area of research. Research within the current spectrum of CIM indicates some ambiguities surrounding corporate identity in higher education.However, very few studies are available in the field of corporate identity within universities.Accordingly, the objective of this study is to examine the relationships between university’s CIM and organizational performance, and also to identify the relevant underlying mechanisms of CIM in Malaysian higher-education sector.Based on a review of the existing literature in a range of fields, this study proposes a conceptual model of the positive relationships between CIM activities in universities with the internal brand, transformational leadership, and organizational culture.The internal brand communication, transformational leadership characteristics of the immediate leader and organizational culture of the university are included in the model as determinants of CIM activities.The proposed conceptual model is developed based on marketing control theory (Jaworski, 1988) combined with transformational leadership theory (Burns, 1978), and social learning theory (Bandura, 1977).The researchers expect this research to make several theoretical, managerial and policy contributions. For example, the institutions which want to build organizational performance from the academic staff should ensure that the CIM, internal brand, organizational culture and leadership move in the right direction.